Understanding the role of plant lipids in cold acclimation, a study of Arabidopsis thaliana and the extremophile Eutrema salsugineum - Silvestre, Susana (2020)
Temperature fluctuations caused by the consequences of climate change and global warming will increase adaptive pressure on plants and crops, limiting their distribution and yield. Increasingly, with periods of unpredictable cold including unseasonal chilling and sub-zero temperatures, understanding the mechanisms of plant adaptation is of greater significance. Cold acclimation is the adaptive process that plants initiate to allow survival even under freezing temperatures. However, this is a multifactorial process involving molecular, metabolic and physiological adaptations, which remains to be fully understood. Lipid metabolism is a significant proportion of cellular activity, involving the breakdown or storage of fats for energy and the synthesis of structural (plasma- and endo-membranes) and functional (signalling and protective) lipids. The nature and diverse structures found in plant lipids provide a source of properties that, fully understood, could revolutionise the way crops are designed. This thesis was developed with the aim to further our understanding of the role of plant lipids in the cold acclimation process. The work was developed in the plant model Arabidopsis thaliana and utilised the extremophile Eutrema salsugineum as an exemplar. Cold-induced transcriptomic changes were analysed, which led to the identification of a phytyl ester synthase and a proton gradient regulator gene as key candidates for cold acclimation. The role of these genes was tested in a novel fluorescence-based screen and confirmed using lipidomic profiling. The capacity to remodel membrane composition and maintain structural integrity is a key adaptive strategy, therefore the role of the Eutrema long-chain base Δ8-desaturase in sphingolipid remodelling during cold stress was determined. Lastly, a focus was given to Eutrema as an extremophile plant model where a germination, transformation and genome editing protocols were developed to produce mutants deficient in chloroplast-produced trienoic acids essential to cold acclimation.